2013
DOI: 10.1186/1471-2334-13-199
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and factors associated with carriage of multi-drug resistant commensal Escherichia coliamong women attending antenatal clinics in Central India

Abstract: BackgroundCommensal Escherichia coli are a prominent reservoir of genes coding for antibiotic resistance and also responsible for endogenous infections in pregnant women. We studied the factors in pregnant women associated with carriage of multi-drug resistant (MDR) E. coli and genetic determinants of antibiotic resistance in them.MethodsWomen attending to Obstetric and Gynaecology department outpatient clinics for routine antenatal check-up were administered a questionnaire. Peri-anal swabs were collected for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
46
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 35 publications
(53 reference statements)
10
46
2
Order By: Relevance
“…Our estimation of the ESBL-PE colonization rate among pregnant women in the community (18.5%) is similar to those reported in Tanzania (15% in 2013) (15) and India (15% in 2007 to 2009) (16). A previous community-based study conducted in Madagascar in 2009 estimated an ESBL-PE carriage rate of 10% (17).…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Our estimation of the ESBL-PE colonization rate among pregnant women in the community (18.5%) is similar to those reported in Tanzania (15% in 2013) (15) and India (15% in 2007 to 2009) (16). A previous community-based study conducted in Madagascar in 2009 estimated an ESBL-PE carriage rate of 10% (17).…”
supporting
confidence: 74%
“…Living in an individual house and having a private inside access to drinking water were associated with ESBL-PE colonization. These conditions reflect a higher socioeconomic status in a globally underprivileged population and may correlate with more frequent access to health care services or a higher antibiotic consumption (16). However, we did not find any association between individual antibiotic consumption and ESBL-PE colonization.…”
contrasting
confidence: 55%
“…The presence of PMQR gene in resistant isolates was 6.75%. This agrees with other studies that reported prevalenece of PMQR gene [30,31].…”
Section: Discussionsupporting
confidence: 83%
“…Also a study by [31] recorded aac(6')-Ib-cr gene (95%) as the most common PMQR gene isolated from multidrug resistant E. coli in India. This agrees with the result obtained in this study as a high prevalence of isolation of the aac(6')-Ib-cr was recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Poor health and sanitation conditions were set forth to increase the spread of ESBL by fecal-oral route and compliance with the rules of hygiene was suggested to be worth investigation (37). In a study in India, the ESBL fecal carriage rate was high in people with high levels of education and this situation was thought to be associated with the fact that it was easier for these people to obtain antibiotics (38). In our study, the carriage rates in university graduates were determined to be significantly lower.…”
Section: Discussionmentioning
confidence: 99%